The Interrater and Intrarater Reliability of the Humeral Head Ossification System and the Proximal Femur Maturity Index Assessments for Patients with Adolescent Idiopathic Scoliosis - Wang, Huan; Lu, Qing-da; Liu, Chen-xin; Yang, Shuai; Qi, Bo-hai; Bai, Huan-an; Qu, Ji-ning; Yang, Ye; Jin, Xiao-hui; Yang, Ming; Su, Fei; Yang, Ya-ting; et al. (Frontiers in Pediatrics, 2023)
Background Skeletal maturity can evaluate the growth and development potential of children and provide a guide for the management of adolescent idiopathic scoliosis (AIS). Recent studies have demonstrated the advantages of the Humeral Head Ossification System (HHOS) and the Proximal Femur Maturity Index (PFMI), based on standard scoliosis films, in the management of AIS patients. We further assessed the HHOS and the PFMI method's reliability in the interrater and intrarater. Methods The data from 38 patients, including the humeral head and proximal femur on standard scoliosis films, were distributed to the eight raters in the form of a PowerPoint presentation. On 38 independent standard spine radiographs, raters utilized the HHOS and PFMI to assign grades. The PPT sequence was randomly changed and then reevaluated 2 weeks later. For every system, the 95% confidence interval (95% CI) and intraclass correlation coefficient (ICC) were calculated to evaluate the interrater and intrarater reliability. Results The HHOS was extremely reliable, with an intraobserver ICC of 0.802. In the first round, the interobserver ICC reliability for the HHOS was 0.955 (0.929–0.974), while in the second round, it was 0.939 (0.905–0.964). The PFMI was extremely reliable, with an intraobserver ICC of 0.888. In the first round, the interobserver ICC reliability for the PFMI was 0.967 (0.948–0.981), while in the second round, it was 0.973 (0.957–0.984). Conclusions The HHOS and PFMI classiﬁcations had excellent reliability. These two methods are beneficial to reduce additional exposure to radiation and expense for AIS. There are advantages and disadvantages to each classification. Clinicians should choose a personalized and reasonable method to assess skeletal maturity, which will assist in the management of adolescent scoliosis patients.